Business and Leisure Ã¢â‚¬Å“BleisureÃ¢â‚¬Â in Organization: Antecedents and Outcomes - Adhiatma, Ardian; Muna, Nailil; Fachrunnisa, Olivia (JDM (Jurnal Dinamika Manajemen), 2019)
The purpose of this study is to explore the concept of bleisure (business and leisure) in an organization along with its antecedents and outcomes. Bleisure is a combination of completing work and entertainment or a pleasant situation at the same time. The sample used in this study were 106 respondents who work in Event Organizer (EO). Data collection methods in this study used questionnaires. Data was analyzed by using regression test. The results of this study indicate that if people work in an organization that combines business and leisure (bleisure), they will have the creativity and high innovation performance, and the application of business and leisure (bleisure) can be achieved through mobile working style and gamification. Bleisure or a combination of fun activities and work can enhance creative intelligence and innovation performance for individuals in completing work, every person will be more creative and innovative. Leisure and work are related things, when individuals are burdened with assignments, the application of leisure in an organization is one of the effective things.